Accelerometers thresholds to estimate physical activity intensity in children and adolescents: a systematic review. DOI: 10.5007/1980-0037.2012v14n1p101 - Felipe Fossati Reichert; Edio Luiz Petroski; Marcelo Romanzini (Universidade Federal de Santa Catarina, 2012)
The aim of this study was to verifiy the validity (criterion) and generality (cross-validity) of accelerometer thresholds to distinguish different physical activity intensities and identify sedentary behaviors in children and adolescents. A systematic literature review was conducted in Pubmed, Scopus, Sports Discus and Web of Science databases. Inclusion criteria were: a) derivation and/or validation of accelerometers thresholds related to intensity of physical activity in youth (2 to 18 years); b) use of indirect calorimetry or direct observation as reference method; c) original research article published in English, Portuguese or Spanish. Nineteen studies were selected. Accelerometers most investigated were ActiGraph, RT3 and Actical. Thresholds showed good to moderate validity in the calibration phase (sensitivity = 68 to 100%; specificity = 61 to 100%). Generalizability of the thresholds were higher when they were tested on samples (Kappa = 0.72 to 0.91; sensitivity = 79 to 94%; specificity = 72 to 98%) than in independent activities (Kappa = 0.46 to 0.71; sensitivity = 27 to 97%; specificity = 52 to 95%). One calibration study tested the validity of thresholds in samples and independent activities, and only a validation study of thresholds was found. In conclusion, limited information was found on the majority of accelerometers thresholds to monitoring physical activity of children and adolescents. Validation studies are needed to identify appropriate thresholds for each type of accelerometer.